DESIGN OF A LABORATORY SCALE SWIRLING FLUIDIZED BED DRYER FOR ROUGH RICE - Andika Putra, Satya
Drying is one of the necessary process in post-harvest handling to increase the shelf time of the agricultural products. Grains are one of the agricultural products that require drying process. One of the dryers type that can be used to dry grains of agricultural products is swirling fluidized bed dryer (SFBD). SFBD can be used to dry the granules particles better than the fluidized bed dryers. Unfortunately in Indonesia SFBD has not done much research, especially for grains of agricultural products. Therefore we need a study of SFBD to dry grains of agricultural products, especially for rough rice. Rough rice is chosen because rice is an agricultural commodity which until now still dominates in Indonesia, so the result of this research is expected to be utilized by the people of Indonesia as an alternative to dry the rough rice, especially during rainy season. This research is to design for laboratory scale of SFBD to dry the rough rice. Rough rice Ciherang used in this study. The steps taken are literature studies related to rough rice and SFBD, calculation of minimum fluidization velocity, outer wall design, center body, distributor, calculation of drying air flow rate, design of inlet air intake with one inlet, drawing prototype of dryer, simulating airflow using Computational Fluid Dynamic (CFD), making of prototype of drying tool, testing of prototype of empty load dryer, validation simulation use testing result data, design of inlet air intake with two inlet, simulating airflow using CFD, analyzing airflow simulation result, conducting analytical studies of heat transfer, heating design, and drying capacity. The results of design laboratory scale of SFBD for rough rice, outer walls is cylindrical with a diameter 400 mm and height 500 mm, plenum center body is cylindrical with a diameter 300 mm and height 260 mm, column center body is conical with a diameter 300 mm and height 210 mm, distributor consisting of a hundred blades with a 45 ° inclination angle to horizontal plane and a width of 50 mm and a height of 37.5 mm, two inlet air intakes with a 58 mm diameter cylinder shape and a length of 600 mm. The calculation result of the minimum fluidization velocity is 6.96 m/s. Drying chamber (column) is designed with a temperature of 45 ° C. The dryer air is supplied from the heating chamber with a U-finned air heater type with total energy of 3722 W. The drying capacity is calculated at 709.5 g of rough rice per hour. The simulation results of airflow using CFD found that the airflow on the SFBD with two air inlets resulted the distribution of air velocity out of the distributor more evenly compared to the SFBD with one air inlet.